The role of the US National Guard the Army and NATO forces before, during and after Hurricane Katrina - Derlatka, Katarzyna (Armia kontra natura, 2020)
At the turn of August and September 2005, the American power turned out to be helpless against the strength of hurricane Katrina, which destroyed 234 thousand km² in 19 states. Katrina was called the biggest catastrophe for the United States, it was a lesson in humility for the authorities that country should be prepared for any eventuality, anticipate as many scenarios as possible for each identified threat. One of the reasons for significant human and material losses was the lack of a developed and implemented national framework for emergency response, which would presume compulsory earlier evacuation of the population and faster involvement of services and the army. 72 000 soldiers, including as many as 50 000 National Guard soldiers, participated in the rescue operation during and after hurricane Katrina. Ships, transport aircraft and helicopters were sent to help the victims of the disaster. The army helped in the distribution of food and medicine, in evacuation, in rescue operations, the transport of gifts and necessary livelihood. Military operations conducted in response to hurricane Katrina were multi-faceted. In the response phase search and rescue operations were carried out mainly by helicopters, evacuation of people by surface transport and assistance operations, including transport of supplies, garbage removal, restoration of critical transport and communication networks as well as search and rescue operations. The scale of damage during hurricane Katrina also necessitated the use of NATO support.